Neurobiology of infantile autism (Research, Society and Development, 2021)
Objective: to discuss the neurobiological characteristics of Autism Spectrum Disorder (ASD) in children. Methodology: a narrative review was conducted based on articles from the last 10 years (2010-2020) published on the databases PsycINFO, Medline, PubMed, SciELO, LILACS and Periódicos CAPES. The descriptors used are “Infantile Autism”, “Autism Disorder”, “Childhood”, “Vital Cycle”, “Child Neurodevelopment”, “Neurobiology”, “Neuroscience”, “Neuroanatomy”, “Autism Spectrum Disorder” and the Boolean “AND”. The material was entirely read, categorized, and subsequently, critically analyzed.  Results and discussion: among ASD individuals there is a decrease in connectivity between the medial prefrontal cortex and the posterior cingulate cortex; this decrease is related to a reduced social function when compared to healthy children. Similar alteration was found regarding the frontoparietal network which related to the repetitive behaviors observed in the disorder. There also is a hypothesis concerning cerebellar dysfunction and more specifically, that the Tuberous Sclerosis Complex 1 (TSC 1) deletion – gene that encodes the hamartin protein – in the Purkinje cells reflects on the social and behavioral deficits among ASD individuals. Furthermore, it is suggested that the disorder phenotype is associated with a disturbance in the networks that connect the cerebellum to the medial prefrontal cortex also due to a higher activation in the last region. Conclusion: there still is no satisfactory and pathognomonic conclusion regarding the neurobiology of ASD in children. The most common neurofunctional alterations in ASD are related to cerebellar networks and Purkinje cells.